Implementasi Aplikasi Absensi Guru Menggunakan QR Code Dengan Metode Logika Fuzzy Berbasis Website Pada Pondok Pesantren An Nawawi - Irham Maulana; Debby Rahadian Baskhara (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
In managing teacher attendance, An Nawawi Islamic Boarding School in Gunung Sindur, Bogor, still records attendance manually using stationery and paper by the teacher on duty. The attendance sheets are then submitted to the boarding school management department as records. This makes it difficult to summarize attendance because each monthly attendance record sheet must be evaluated individually. QR codes are an idea that can facilitate the evaluation of attendance data, which is then read on a web-based application. The use of QR codes is essential for efficiency and effectiveness in attendance activities. Of course, a method is also needed to simplify the data validation process. With this background, this research aims to implement a web-based teacher attendance application that utilizes QR codes and uses the Fuzzy Logic method to improve the validity of teacher attendance data. QR codes are used as a practical attendance medium, while Fuzzy Logic is applied to handle uncertainty in the attendance process, such as lateness or other special conditions. This system is developed using website-based software to make it easily accessible and integrated. The research results are expected to provide a more effective attendance solution while reducing errors in manual recording. System testing includes aspects of functionality, QR-Code scanning speed, and the accuracy of Fuzzy Logic in evaluating attendance status.